NT

(3n-1) chia hết cho n+2

(5n+3) chia hết cho (2n+1)

(3-n mũ 2 ) chia hết cho n-1

NN
10 tháng 2 2019 lúc 19:40

\\la cai chich me may

Bình luận (0)
H24
10 tháng 2 2019 lúc 19:51

\(3n-1⋮n+2\)

\(\Rightarrow3n+6-7⋮n+2\)

\(\Rightarrow3\left(n+2\right)-7⋮n+2\)

Do : \(3\left(n+2\right)⋮n+2\)suy ra : \(7⋮n+2\)

\(\Rightarrow n+2\inƯ\left(7\right)=\left\{-7;-1;1;7\right\}\)

\(\Rightarrow n\in\left\{-9;-3;-1;5\right\}\)

Bình luận (0)
TD
10 tháng 2 2019 lúc 19:56

3n - 1 = 3n + 6 - 7 = 3(n + 2) - 7

Để \(\left(3n-1\right)⋮\left(n+2\right)\) thì \(7⋮\left(n+2\right)\)

=> \(n+2\inƯ\left(7\right)=\left\{-7;-1;1;7\right\}\)

Nếu n + 2 = -7 => n = -7 - 2 => n = -9

Nếu n + 2 = -1 => n = -1 - 2 => n = -3

Nếu n + 2 = 1 => n = 1 - 2 => n = -1

Nếu n + 2 = 7 => n = 7 - 2 => n = 5

Vậy \(n\in\left\{-9;-3;-1;5\right\}\)

Bình luận (0)
NH
10 tháng 2 2019 lúc 19:59

a)( 3n - 1 ) \(⋮\)n + 2  \(\Rightarrow\) 3(n+2)\(⋮\)n+2   => 3n+4 \(⋮\) n+2

=>  3n+4  -  3n-1  \(⋮\)n+2

3\(⋮\)n+2

n+213
n-11

vậy n = -1 : 1

b) 5n+3\(⋮\)2n+1 => 2(5n+3) - 5(2n+1)\(⋮\)2n+1

10n+3-10n+5 \(⋮\)2n+1

2 chia hết 2n+1

2n+112
n0loại

vậy n = 0

Bình luận (0)
NH
10 tháng 2 2019 lúc 20:07

c) (3-n\(^2\))\(⋮\)n-1

Bình luận (0)

Các câu hỏi tương tự
NP
Xem chi tiết
VL
Xem chi tiết
DA
Xem chi tiết
VN
Xem chi tiết
NT
Xem chi tiết
DQ
Xem chi tiết
CT
Xem chi tiết
H24
Xem chi tiết
LT
Xem chi tiết